(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article is devoted to the process of differential education and its effective application in the process of primary education. The concept of education and differential education and their essence, the history of differential education, scientists who contributed to this field of education, the purpose of applying differential education in the field of primary education, the purpose of this education tasks, advantages and disadvantages, technologies used in the process of educational application are analyzed. Methodological approaches and practical recommendations for the organization of differential education are also given.